Facilitation of molecular motion to develop turn-on photoacoustic bioprobe for detecting nitric oxide in encephalitis - Ji Qi (Nature Portfolio, 2021)
Nitric oxide plays key roles in regulating many pathological processes and it is important to monitor NO and related diseases. Here, the authors report on the development of a molecular motion based NO responsive photoacoustic probe and demonstrate application in detecting encephalitis in vivo.